Blood pressure control in hypertensive patients within Family Health Program versus at Primary Healthcare Units: analytical cross-sectional study - Martins, Telma Lima; Atallah, Álvaro Nagib; Silva, Edina Mariko Koga da (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Hypertension is a public health problem due to its high prevalence and longterm cardiovascular complications. In Brazil in 2005, cardiovascular diseases were responsible for 28% of all deaths. Efforts are being made within primary care to achieve adequate hypertension control. The Family Health Program (FHP) has the aims of promoting quality of life and intervening in factors that put this at risk. The objective of this study was to evaluate the rate of blood pressure control among patients followed up at FHP units compared with those at primary healthcare units (PHUs). DESIGN AND SETTING: Analytical cross-sectional study in the municipality of Petrópolis, Rio de Janeiro, from January to December 2005. METHODS: Five hundred patients with a diagnosis of hypertension were included: 250 were being followed up at two FHP units and 250 at two PHUs. The diagnosis of hypertension was based on the Fourth Brazilian Hypertension Consensus, and the patients needed to have been under follow-up at the units for at least 12 months. Patients’ blood pressure was considered to be under control if it was less than 140/90 mmHg at the last consultation. RESULTS: Blood pressure was under control in 29.2% (n = 73) at FHP units and 39.23% (n = 98) at PHUs (odds ratio = 0.64; confidence interval = 0.44-0.93; P = 0.024). CONCLUSION: Blood pressure control was better among patients followed up at PHUs than among those followed up at FHP units.